Preparation of Shrikhand from goat milk using probiotic cultures - V B Shinde; S S Kamble; D H Kankhare; PT Dhole (Journal of Livestock Biodiversity, 2025)
Shrikhand is a traditional fermented milk product of Indian origin and is popular in western parts of India. Starter culture is known to play vital role in the development of body, texture, flavor and aroma in the finished products and contributes significantly towards overall acceptance of products by the consumer. In investigation the probiotic cultures used in preparation of shrikhand were Lb. acidophilus and Lb. delbruekii ssp.bulgaricus alone and in combination and LF-40 culture alone as a control. Probiotic cultures viz., Lb.7 acidophilus and Lb. bulgaricus alone and in combination containing viable lactobacilli counts more than 10 c.f.u./g in fresh as well as in stored shrikhand. The results revealed that organoleptically acceptable shrikhand from goat milk can be prepared by using probiotic cultures viz., Lactobacillus acidophilus and Lactobacillus delbrueckii ssp. bulgaricus alone and in combination. There was non significant difference observed for sensory evaluation for all treatments. Flavour score observed highest in (8.00) stored shrikhandprepared by combination of Lactobacillus acidophilus and Lactobacillus delbrueckii. The probiotic shrikhand can be prepared and stored at 7 + 1 C for a week and possessing good organoleptic quality with therapeutic quality.